Gamma irradiation influence on mechanical, thermal and conductivity properties of hybrid carbon nanotubes/montmorillonite nanocomposites - Tarawneh, Mou'ad A. (Radiat Phys Chem Oxf Engl 1993, 2021)
A thermoplastic elastomer (TPE) based nanocomposite with the same weight ratio of hybrid nanofillers composed of carbon nanotubes (CNTs) and montmorillonite nanoclay (DK4) was prepared using a melt blending technique with an internal mixer. The TPE composite was blended from polylactic acid (PLA), liquid natural rubber (LNR) as a compatibilizer and natural rubber (NR) in a volume ratio of 70:10:20, respectively. The weight ratio of CNTs and DK4 was 2.5 wt%. The prepared samples were exposed to gamma radiation at range of 0–250 kGy. After exposure to gamma radiation, the mechanical, thermo-mechanical, thermal and electrical conductivity properties of the composites were significantly higher than unirradiated TPE composites as the irradiation doses increased up to 150 kGy. Transmission electron microscopy (TEM) micrographs revealed the good distribution and interaction between the nano-fillers and the matrix in the prepared TPE hybrid nanocomposites. In summary, the findings from this work definite that gamma irradiation might be a viable treatment to improve the properties of TPE nanocomposite for electronic packaging applications.